Essential ethnographic methods : a mixed methods approach, 2nd edition - Schensul,Jean j.; Colorado-Boulder, Margaret D. LeCompte University of. ([S.l.] : AltaMira Press, 2012)
Essential Ethnographic Methods introduces the fundamental, face-to-face data collection tools that ethnographers and other qualitative researchers use on a regular basis. It provides ethnographers with tools to answer the principal ethnographic questions about setting, participants, activities, behavior, and more. The essential (3z(Bmixed(3y (Bmethods for collecting data include open-ended and focused listening, questioning strategies, participant and non-participant observation, recording techniques, visual recall, mapping the environments and contexts in which participant behavior occurs, and engaging in ethnographically informed survey research. Because these data collection strategies require ethnographers to become involved in the local cultural setting and to acquire their experience through hands-on experience, the essential tools also allow them to learn about new situations from the perspective of an "insider.(3y (BWith these detailed instructions, the quality and scope of the data ethnographers collect are sure to be improved.s